TATA KELOLA TI PADA ORGANISASI KESEHATAN: TINJAUAN LITERATUR SISTEMATIS MENGENAI FRAMEWORK, TANTANGAN, DAN MANFAAT : IT GOVERNANCE IN HEALTHCARE ORGANIZATIONS: A SYSTEMATIC LITERATURE REVIEW OF FRAMEWORKS, CHALLENGES, AND BENEFITS - Maharani Swastika; Taufik Akbar; Aris Puji Widodo; Kusworo Adi; Bambang Sugeng Suryatna (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Information Technology (IT) in the healthcare sector has driven the growing need for effective IT governance to ensure the security, efficiency, and quality of healthcare services. This study provides a comprehensive review of Information Technology (IT) Governance used in the healthcare sector, particularly in hospitals, by analyzing frameworks, their implementation challenges, and evaluating their impact on service quality and operational efficiency. The method used is a systematic literature review based on PRISMA guidelines of 34 international articles published between 2020 and 2025. The sources identified that COBIT is the dominant best practice framework used to align IT with organizational goals and ensure regulatory compliance. In addition, TOGAF is relevant for auditing, risk management, and enterprise architecture design. Specialist frameworks such as blockchain are proposed for higher data security and integrity. Although these frameworks support improved patient outcomes, data security, and operational efficiency, their implementation is hampered by leadership challenges, technical (such as poor infrastructure and legacy system integration), and complex data regulatory compliance issues.